Engendering drug problems: Materialising gender in the DUDIT and other screening and diagnostic ‘apparatuses’ - Dwyer, Robyn; Fraser, Suzanne (Elsevier BV, 2017)
© 2017 Elsevier B.V. It is widely accepted that alcohol and other drug consumption is profoundly gendered. Just where this gendering is occurring, however, remains the subject of debate. We contend that one important and overlooked site where the gendering of substance consumption and addiction is taking place is through AOD research itself: in particular, through the addiction screening and diagnostic tools designed to measure and track substance consumption and problems within populations. These tools establish key criteria and set numerical threshold scores for the identification of problems. In many of these tools, separate threshold scores for women and men are established or recommended. Drawing on Karen Barad's concept of post-humanist performativity, in this article we examine the ways in which gender itself is being materialised by these apparatuses of measurement. We focus primarily on the Drug Use Disorders Identification Test (DUDIT) tool as an exemplar of gendering processes that operate across addiction tools more broadly. We consider gendering processes operating through tools questions themselves and we also examine the quantification and legitimation processes used in establishing gender difference and the implications these have for women. We find tools rely on and reproduce narrow and marginalising assumptions about women as essentially fragile and vulnerable and simultaneously reinforce normative expectations that women sacrifice pleasure. The seemingly objective and neutral quantification processes operating in tools naturalise gender as they enact it.